Code-Mixing on Lyrics of Batak Pop Songs Martina I Love You from Trio Romansa - Abdul Gapur; Muhammad Pujiono; Taulia Taulia (Politeknik Negeri Padang, 2018)
This paper discusses code-mixing that occurs in the lyrics of Batak pop songs entitled